1981
DOI: 10.1055/s-2007-1023459
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural Instillation of Streptokinase Effects on Systemic Fibrinolysis

Abstract: Un ive rsity of Go thenburg. Go thenbu rg, Swe de n Summary Ten cons ec ut ive pa tien ts aged 2 5 to 75 with po stoperat ive emp yema or hemothorax co nven tionally t reated with drainage w itho ut sufficient effe ct wer e given int rapleural lnst ltlations of st rep t ok inase (K ab iki nase® , 250 .00 0 IE ) f or 4 hou rs!) . Th e eff ects on systemic fibrin oly sis were st ud ied .Venous bl ood samp les for dete rm inati on o f f ib ri noly ti c activity on fibrin plate s, plasmin ogen , Qrant iplasmin. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 1 publication
0
25
0
1
Order By: Relevance
“…Our observations are in accord with those in previous reports. Berglin and coworkers (33) did not observe any effects on systemic fibrinolytic activity, ␤ 2 -macroglobulin levels, or thrombin times with the intrapleural instillation of SK in 10 consecutive patients with empyemas or hemothoraces. In addition, they reported a slight increase in plasminogen, ␤ 2 -antiplasmin levels, and fibrinogen, but these alterations probably represented an acute-phase reaction.…”
Section: Discussionmentioning
confidence: 89%
“…Our observations are in accord with those in previous reports. Berglin and coworkers (33) did not observe any effects on systemic fibrinolytic activity, ␤ 2 -macroglobulin levels, or thrombin times with the intrapleural instillation of SK in 10 consecutive patients with empyemas or hemothoraces. In addition, they reported a slight increase in plasminogen, ␤ 2 -antiplasmin levels, and fibrinogen, but these alterations probably represented an acute-phase reaction.…”
Section: Discussionmentioning
confidence: 89%
“…[46]). However, TEMES et al [42] in their series observed a case of significant local bleeding which required thoracotomy.…”
Section: Fibrinolytic Agentsmentioning
confidence: 99%
“…Activation of plasmin triggers a proteolysis cascade that degrades the fibrin in the abscess [12,16]. Another fibrinolytic agent, streptokinase, has been used to treat pleural empyema with satisfactory results [27][28][29], but its antigenic blockage effect is a great disadvantage, in spite of its favorable cost compared to urokinase [15]. Intracavitary urokinase (pleural cavity and abscessed cavities) does not have systemic effects [12].…”
Section: Discussionmentioning
confidence: 99%